PROCESSES USED IN RISK MANAGEMENT - Corina-Maria, DUCU (Strategii Manageriale, 2014)
In today's world, entities must pay a particular attention to the risks they have to face, risks that affect the developed activities. This requires the development of some processes of risk management, internal control and corporate governance, whose main purpose is to reduce them to a significant level.